2016
DOI: 10.1371/journal.pone.0153955
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Polymorphisms in Invasive Fire Ants

Abstract: In the Found or Fly (FoF) hypothesis ant queens experience reproduction-dispersal tradeoffs such that queens with heavier abdomens are better at founding colonies but are worse flyers. We tested predictions of FoF in two globally invasive fire ants, Solenopsis geminata (Fabricius, 1804) and S. invicta (Buren, 1972). Colonies of these species may produce two different monogyne queen types—claustral queens with heavy abdomens that found colonies independently, and parasitic queens with small abdomens that enter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…For example, discrimination against alien conspecific eggs occurs in the social wasp Polistes biglumis, and it has been suggested that brood discrimination abilities evolved as counter-adaptations against intra-and interspecific social parasitism [59]. Similarly, in ants of the genera Myrmica and Solenopsis, conspecific queens can act as intraspecific parasites [72,73]. In F. fusca, relatedness among nest-mate queens is highly variable [40,74], and several mitochondrial lineages may be present within a colony (H Johansson 2017, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…For example, discrimination against alien conspecific eggs occurs in the social wasp Polistes biglumis, and it has been suggested that brood discrimination abilities evolved as counter-adaptations against intra-and interspecific social parasitism [59]. Similarly, in ants of the genera Myrmica and Solenopsis, conspecific queens can act as intraspecific parasites [72,73]. In F. fusca, relatedness among nest-mate queens is highly variable [40,74], and several mitochondrial lineages may be present within a colony (H Johansson 2017, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Research on ant body size has focused largely on workers (Cerdá & Retana, 1997; Kaspari, 1996; Powell & Franks, 2006; Schöning, Kinuthia, & Franks, 2005); few studies examined size variation in males (Abell et al., 1999; Stürup, den Boer, Nash, Boomsma, & Baer, 2011) or queens (Helms & Godfrey, 2016; Rüppell & Heinze, 1999; Wiernasz & Cole, 2003) despite their crucial role within the colony. Here we find that members of the reproductive castes are smaller in colder environments, which could lower their fecundity (Vargo & Fletcher, 1989; Wiernasz, Sater, Abell, & Cole, 2001 but see Stürup et al, 2011), longevity (Calabi & Porter, 1989), and dispersal ability (Helms, 2018; Sundström, 1995 but see Davidson, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they need large gasters to contain their reproductive organs (Trible & Kronauer, 2017), but also large thoraxes to accommodate their flight muscles (Keller et al., 2014), and metabolic reserves, especially in claustral species (Peeters, 2012). Thus, for the reproductive castes, an increase in gaster size might be counterbalanced by an increase in thorax size to conserve a similar flight muscle to weight ratio (Helms & Godfrey, 2016), thus heightening fecundity while minimizing drawbacks on dispersal ability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, globally invasive fire ant species Solenonopsis geminata (Fabricius, 1804) and S. invicta Buren, 1972 show dispersal polymorphism of the reproductive queens. These species have heavier claustral queens and lighter parasitic queens, the latter is able to fly much longer distances (HELMS and GODFREY, 2016). The silent switch from the "dispersal phase" to the "reproductive phase", including the histolysis of the flight muscles is documented in many insect orders, and it can be very widespread (see the reviews in the Introduction).…”
Section: Are Wing Polymorphic Insects Resilient Colonists?mentioning
confidence: 99%